2021
DOI: 10.1111/1462-2920.15800
|View full text |Cite
|
Sign up to set email alerts
|

Differential bacterial endophytome in Foc‐resistant banana cultivar displays enhanced antagonistic activity against Fusarium oxysporum f.sp. cubense (Foc)

Abstract: Diverse endophytes with multiple functions exist in different banana cultivars. However, the diversity of cultivable bacterial endophytome that contributes to antifungal activity against Fusarium oxysporum f.sp. cubense (Foc) in resistant and susceptible banana cultivars is mostly unknown. In the present study, we isolated bacterial endophytes from resistant Yengambi KM5 (AAA) and susceptible banana cultivar Ney Poovan (AB) to determine the diversity of cultivable bacterial endophytes. Our study revealed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…It was reported that B. paraconglomeratum YEBPT2 isolated from banana contributed to antifungal activity against Fusarium oxysporum f.sp. cubense (Foc), and nine bioactive metabolites were identified as diethyl hydrazine, carbonic acid, nitrosopyrrolidine, 4H-pyran, valeric acid, butanoic acid, trioxsalen, deoxy-d-mannoic acid, and amino caprylic acid [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that B. paraconglomeratum YEBPT2 isolated from banana contributed to antifungal activity against Fusarium oxysporum f.sp. cubense (Foc), and nine bioactive metabolites were identified as diethyl hydrazine, carbonic acid, nitrosopyrrolidine, 4H-pyran, valeric acid, butanoic acid, trioxsalen, deoxy-d-mannoic acid, and amino caprylic acid [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of soil and rhizosphere microbial diversity and composition is hence fundamental to implement sustainable crop management, as well as to determine the impact of one or more biological/technical factors on the indigenous BCA. Progress has been achieved in determining the links between Fusarium wilt and banana-associated microorganisms (Effendi et al, 2019 ; Kaushal et al, 2020 ; Gómez-Lama Cabanás et al, 2021 ; Ravi et al, 2021 ). However, the potential of soil microorganisms to manage plant production in a more sustainable way, relying solely on indigenous species, is not yet fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial microorganisms that contribute to plant production include species acting as generalists or, on the contrary, inhabiting specific trophic niches, ranging from endophytes to pathogens or BCA, which affect plant health and thus farm productivity (Bulgarelli et al, 2013 ; Xue et al, 2015 ; Granzow et al, 2017 ; Kaushal et al, 2020 ; Zhang et al, 2020 ; Gómez-Lama Cabanás et al, 2021 ; Ravi et al, 2021 ). Apart from plant growth promoters, soil harbors endosymbionts or BCA often specifically associated with their hosts.…”
Section: Introductionmentioning
confidence: 99%
“…cubense antifungal activity in resistant and susceptible banana cultivars. A study in this issue examined the diversity of cultivable bacterial endophytes by isolating them from resistant Yengambi KM5 (AAA) and susceptible Ney Poovan (AB) banana cultivars (Ravi et al ., 2021). This study reported that 56 cultivable bacterial endophytes and six nectar‐associated bacteria were present in YKM5 and 31 cultivable bacterial endophytes within Ney Poovan.…”
mentioning
confidence: 99%